2002
DOI: 10.1348/096317902321119691
|View full text |Cite
|
Sign up to set email alerts
|

The effects of organizational and individual factors on occupational accidents

Abstract: This study examined the relationships between individual psychological, work environment and organizational variables and occupational accidents using structural equation modelling with latent variables. A series of nested explicative models of the relationships between these variables was derived. Data were collected from a wide range of industrial sectors in the Valencia region of Spain using structured interviews. In total, 525 valid questionnaires were completed and these formed the basis for the subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(85 citation statements)
references
References 23 publications
8
73
0
4
Order By: Relevance
“…The safety climate can be grasped by examining perceptions of job conditions and characteristics (Philips et al, 2012;Rysdstedt and Lundh, 2012) and/or by looking at individual attitudes and characteristics (Oliver et al, 2002;Tomas et al, 2011). It may be influenced by leadership style (Zohar and Luria, 2010).…”
Section: Perceived Risk and Safetymentioning
confidence: 99%
“…The safety climate can be grasped by examining perceptions of job conditions and characteristics (Philips et al, 2012;Rysdstedt and Lundh, 2012) and/or by looking at individual attitudes and characteristics (Oliver et al, 2002;Tomas et al, 2011). It may be influenced by leadership style (Zohar and Luria, 2010).…”
Section: Perceived Risk and Safetymentioning
confidence: 99%
“…However, the safety literature suggests that these individual factors are important and should be included in models that seek to explain safety behaviour. Oliver et al (2002) collected data from a wide range of industrial sectors and employed structural equation modelling (SEM) to test models depicting the influence of organizational and individual variables on accidents. They found that individual level variables, including safe behaviour and general health, mediated the indirect effects of the organizational variables.…”
Section: Predictors Of Medication Errorsmentioning
confidence: 99%
“…The literature is not clear on the exact nature of the linkage between Organisational Climate and Violations with some studies suggesting that the linkage is entirely direct (Fogarty 2003) and others suggesting that the effect of Organisational Climate is at least partially mediated by individual factors, notably stress (Lawton & Parker 1998, Cox et al 2002. Figure 1 allows for both of these possibilities with a direct pathway between Organisational Climate and Violations and indirect pathways via Individual Distress and Individual Morale.…”
Section: Building a Measurement And Structural Modelmentioning
confidence: 99%
“…Moreover, the management's commitment to safety and the minimization of the risks at work pave the way for the development of positive attitudes and behaviors by the employees (Coyle-Shapiro & Kessler, 2000). Positive SC encourages employees to engage in SB together with organizational rewards, while negative SC encourages unsafe behaviors (Oliver, Cheyne, Tomas, & Cox, 2002;Tomas, Melia, & Oliver, 1999). At the same time, it provides the sustainability of SB, including positive SC, safety participation and compliance (Cheyne, Cox, Oliver, & Tomas, 1998).…”
Section: The Relationship Between Sc and Sbmentioning
confidence: 99%